2003
DOI: 10.1002/lsm.10203
|View full text |Cite
|
Sign up to set email alerts
|

Acute ultrastructural changes of the trabecular meshwork after selective laser trabeculoplasty and low power argon laser trabeculoplasty

Abstract: Our ultrastructural comparison of the morphological changes after low power ALT and SLT in patients demonstrated that both lasers caused splitting and fragmentation of the trabecular beams of the trabecular meshwork, but the extent of the damage was smaller and the preservation of long-spacing collagen better after SLT than after ALT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0
13

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(77 citation statements)
references
References 16 publications
3
61
0
13
Order By: Relevance
“…This low-power setting indicates that the energy delivered to the eye by SLT is significantly less than that of ALT, which results in less tissue damage to the trabecular meshwork. 6,7 The purpose of this systematic review is to compare SLT to other treatment options in terms of their IOP-lowering effect. This will include only randomised controlled trials (RCTs) in which SLT has been compared to any other treatment options.…”
Section: Introductionmentioning
confidence: 99%
“…This low-power setting indicates that the energy delivered to the eye by SLT is significantly less than that of ALT, which results in less tissue damage to the trabecular meshwork. 6,7 The purpose of this systematic review is to compare SLT to other treatment options in terms of their IOP-lowering effect. This will include only randomised controlled trials (RCTs) in which SLT has been compared to any other treatment options.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] Ultrastructural analysis of the TM in human eyes after SLT showed no alteration of the collagen structure and central core regions of the trabecular beams with no evidence of coagulative damage of the trabecular structure. 14,15 To date, several reports comparing 1801 SLT vs 1801 ALT 13,[16][17][18] and studies evaluating the efficacy and safety of ELT ab interno over one-half of the TM 9,19,20 have been published.…”
Section: Introductionmentioning
confidence: 99%
“…Cvenkal et al performed a similar comparison wherein ALT or SLT were performed on three eyes from patients awaiting enucleation due to choroidal melanoma. 21 In contrast to Kramer and Noecker, these authors found disruption of the trabecular beams after either form of LTP, although less after SLT than ALT. After both ALT and SLT, lasered tissue was sharply demarcated from surrounding tissue with few pigmented cells observed.…”
Section: Histological Studiesmentioning
confidence: 71%
“…Histological studies have confirmed that ALT does not allow for SP, and indeed causes nonselective tissue disruption and photocoagulation of the TM. [19][20][21][22] Laser-mediated photocoagulation of the TM has become, in fact, a primary method of experimentally increasing IOP in primates. 23 SLT, in contrast, has a much shorter pulse duration (3 ns), which prevents heat dissipation outside of pigmented TM cells, thereby permitting greater localization of damage.…”
Section: Selective Laser Trabeculoplastymentioning
confidence: 99%